Interpreting Greek tragedy: myth, poetry, text - Segal, Charles (Cornell Univ. Press, 1986)
Greek tragedy and society -- Greek myth as a semiotic and structural system and the problem of tragedy -- Greek tragedy -- Visual symbolism and visual effects in Sophocles -- Sophocles' praise of man and the conflicts of the Antigone -- The tragedy of the Hippolytus -- The two worlds of Euripides' Helen -- Pentheus and Hippolytus on the couch and on the grid -- Euripides' Bacchae -- Boundary violation and the landscape of the self in Senecan tragedy -- Tragedy, corporeality, and the texture of language -- Literature and interpretation